Where to invade next [videorecording (DVD)] - Moore, Michael, 1954 April 23-; Moore, Michael, 1954 April 23- (Anchor Bay Entertainment, 2016)
Presents the theory that the American dream, all but abandoned in the United States, has been adopted successfully in other countries, including Italy, France, Finland, Slovenia, Germany, Portugal, Norway, Tunisia, and Iceland, looking at such areas as worker benefits, public expenditure for the common good, and state-funded higher education.